Right Traumatic Diaphragmatic Hernia: A Case Report and A review - Thaimi Conde Cueto; Ivette Cepero Pérez; Francisco Olascoaga Pérez; Martha Yudey Rodríguez Pino (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Diaphragmatic hernia constitutes an infrequent form of diaphragmatic disease and a high index of sospecha for its diagnosis. The lesions of the left side seem to be the most frequent according to the review of the medical literature. This is the case of a patient with a 15 year- history of right hemithorax due to car accident who presented to the internal medicine emergency service with weakness and shortness of breath . His skin and mucous membranes were pale and vesicular murmurs were abolished in the inferior two thirds of the right hemithorax. The patient was ordered a complete blood count (CBC), an antero-posterior chest x -ray, an abdominal ultrasound , a thoracic-abdominal ultrasound, a chest computerized axial tomography, respiratory function tests and a medulloculture. The computerized axial tomography revealed a right hemithorax filled with intestinal loops, liver and gallbladder. The patient was surgically treated realizing the presence of a right multivisceral diaphragmatic hernia which was corrected by hernioplasty with prothesis of the polypropylene. The patient recovered satisfactorily . For its uncommon presentation it has been published.